Bilateral Steroid Induced Glaucoma In A 10-year-old Boy - Rosalia Adriani Malika; Lydia Nuradianti (Ikatan Dokter Indonesia Wilayah Jawa Timur, 2023)
Introduction: Topical steroids are used in the treatment of various ocular disorders. However, it can cause numerous side effects. Steroid-induced glaucoma is the most severe complication of the unmonitored use of steroids. It is diagnosed by visual field defects, increased intraocular pressure (IOP), and glaucomatous optic neuropathy (GON) due to prolonged usage of steroids. Case Presentation: a 10-year-old boy presented to the outpatient clinic in Undaan Eye Hospital complaining of headache, re dness and itchiness in both eyes. He started using dexamethasone 0.1% eye drops without a physician's supervision for the last 2 years. Steroid-induced glaucoma was diagnosed in both eyes. Topical and oral glaucoma medications were given. Both eyes IOP were still elevated in the following months. Trabeculectomy in both eyes was performed due to medically uncontrolled glaucoma. Furthermore, both eyes IOP were getting normal without any topical and oral glaucoma medications. Conclusion: Unmonitored steroid usage must be avoided. This case suggests general practitioners and health care providers in the front line be aware of the usage of topical steroids. By increasing awareness concerning steroid-induced glaucoma, a patient's visual acuity can be saved, and irreversible blindness can be prevented, especially in children.